Design of a Heart Rate Monitoring Application Based on Internet of Things (IoT) Technology with WhatsApp Blast - Legiawan, Mohamad Kany; Nazilah, Siti; Nurfauzi, Rizky (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
The highest death rate based on data from WHO (World Health Organization) is due to heart-related diseases. In 2015, more than 17 million people in the world died from heart disease and blood vessel disorders. About 75% of deaths from heart disease occur in developing countries with low to moderate income. Based on SRS (sample registration system) data in 2014, heart disease was the highest cause in Indonesia, namely 12.9%. With IoT (Internet of Things) technology, it can make it easier to provide information to survivors, namely carrying out early heart detection if there are several anomalies that occur in the human body, especially heartbeats that do not comply with the provisions. Utilizing the Max30102 sensor in collaboration with several other IoT devices can be integrated with a web-based system which is used for monitoring based on incoming data from IoT devices. This system is capable of recording heart data in humans in real time by providing notifications to heart survivors via WhatsApp blasting technology.